The Hill: A Romance of Friendship - Vachell, Horace Annesley, 1861-1955 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Hill: A Romance of Friendship" by Horace Annesley Vachell is a novel written in the early 20th century. The book follows the life of John Verney as he navigates his new beginnings at Harrow School, a prestigious British institution steeped in tradition. Through the lens of friendship and rivalry, it explores themes of youth, identity, and the challenges of adapting to a new environment, particularly focusing on John's relationships with his classmates, including the charming Desmond and the enigmatic Scaife. The opening of the novel introduces young John Verney as he arrives at Harrow, accompanied by his uncle, who offers him words of encouragement amidst his feelings of apprehension and homesickness. As the train departs, John reflects on the impending changes in his life and the excitement of boarding at the elite Manor house, despite its recent decline under the watch of the unpopular housemaster, Rutford. John$1 (Bs initial encounters with other boys set the stage for the complex dynamics of friendship, as he navigates the social hierarchies of school life while yearning for acceptance and camaraderie amidst both support and rivalry from his peers. The narration paints a vivid picture of the youthful spirit and the bittersweet essence of growing up. (This is an automatically generated summary.)s
Release date is 2007-01-04
E-text prepared by Al Haines
Keywords: Boys -- Conduct of life -- Juvenile fiction; Social classes -- England -- Juvenile fiction; Friendship -- Juvenile fiction; Snobs and snobbishness -- Juvenile fiction; Harrow School -- Juvenile fiction; Schools -- England -- Juvenile fiction